Major infections, secondary cancers and autoimmune diseases occur in different clinical subsets of chronic lymphocytic leukaemia patients. (February 2017) - Visentin, Andrea; Imbergamo, Silvia; Gurrieri, Carmela; Frezzato, Federica; Trimarco, Valentina; Martini, Veronica; Severin, Filippo; Raggi, Flavia; Scomazzon, Edoardo; Facco, Monica; Piazza, Francesco; Semenzato, Gianpietro; et al.
Abstract: Background: Major infections (MIs), secondary cancers (SCs) and autoimmune diseases (ADs) are the most common and relevant complications in patients with chronic lymphocytic leukaemia. Methods: We performed a single-centre retrospective study to investigate the prevalence of the above quoted complications, the association with most important prognostic markers and their impact on survival (n = 795). Results: Almost one out of three patients experienced at least one complication and only 0.9% of the cohort developed all three complications. One hundred and twenty (20%) subjects developed SC, 98 MI (12%) and 80 AD (10%); these complications seem to occur in a mutually exclusive manner. By Kaplan–Meier analysis we estimated that after 20 years from the diagnosis SC, MI and AD occurred in 48%, 42% and 29% of patients, respectively. Furthermore, we showed that some clinical and biological markers are skewed among patients with different complications and that subjects with MI and SC had a worse prognosis than those with AD and all other patients (p < 0.0001). Conclusions: This study reveals the existence of different clinical subsets of chronic lymphocytic leukaemia patients characterised by an increased and different risk for developing specifically MI, SC and AD. Highlights: Major infections, secondary cancers and autoimmune diseases are the most common complications in patients with chronic lymphocytic leukaemia (CLL). We performed a single-centre retrospective study to investigate the prevalence of these complications in 795 patients with CLL. We identified clinical subsets of CLL patients characterised by an increased and different risk for developing specific kind of complications.